2022
DOI: 10.3389/fpsyg.2022.785301
|View full text |Cite
|
Sign up to set email alerts
|

Talent Cultivation of New Ventures by Seasonal Autoregressive Integrated Moving Average Back Propagation Under Deep Learning

Abstract: This study combines the discovery methods and training of innovative talents, China’s requirements for improving talent training capabilities, and analyses the relationship between the number of professional enrollments in colleges and universities and the demand for skills in specific places. The research learns the characteristics and training models of innovative talents, deep learning (DL), neural networks, and related concepts of the seasonal difference Autoregressive Moving Average (ARMA) Model. These co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Several works were suggested in the literature related to deep learning based talent cultivation quality of software engineering majors, a few recent works are reviewed here, Han et al [20] have suggested that the study gains knowledge of deep learning, neural networks, creative talent traits, and training models associated considering the seasonal variation Model of Autoregressive Moving Average. Autoregressive seasonal integrated moving average regression back propagation was suggested using these ideas.…”
Section: Related Workmentioning
confidence: 99%
“…Several works were suggested in the literature related to deep learning based talent cultivation quality of software engineering majors, a few recent works are reviewed here, Han et al [20] have suggested that the study gains knowledge of deep learning, neural networks, creative talent traits, and training models associated considering the seasonal variation Model of Autoregressive Moving Average. Autoregressive seasonal integrated moving average regression back propagation was suggested using these ideas.…”
Section: Related Workmentioning
confidence: 99%